Increased Arterial Stiffness Is Associated With Reduced Diastolic Function in Youth With Obesity and Type 2 Diabetes - Madsen, Nicolas L.; Haley, Jessica E.; Moore, Ryan A.; Khoury, Philip R.; Urbina, Elaine M. (Frontiers in Pediatrics, 2021)
Background: Increased arterial stiffness is associated with diastolic dysfunction in adults. Data in youth are lacking so we examined the impact of arterial stiffness on diastolic function in youth. Methods: We obtained diastolic function and augmentation index, pulse wave velocity, brachial artery distensibility, and carotid stiffness on 612 youth (10-24 years, 65% female, 38% normal weight, 36% obese and 26% with type 2 diabetes mellitus (T2DM). Participants were classified as compliant (C) versus stiff (S) arteries based on 7 arterial stiffness parameters (Global Stiffness Index (GSI), S=GSI > 4). Mean differences in covariates were evaluated by Student's t-tests. Stepwise regression analysis was performed to determine if GSI was an independent predictor of diastolic function. Results: Lower diastolic function and more adverse CVD risk factors were present in the S group (n=67) than the C group (n=545) (p<0.001). Covariates that were associated with diastolic dysfunction were higher GSI, male sex, higher BMI, and SBP z-score (R2=0.18 to 0.25; p≤0.05). Conclusion: Adverse diastolic function is seen in youth with increased arterial stiffness independent of CVD risk factors. Interventions to improve arterial stiffness prior to clinical onset of diastolic dysfunction are needed to prevent development of heart failure.